Converged services composition with case-based reasoning. (2018) - Chua, Hui Na; Mustapha, S.M.F.D. Syed
In order to achieve the converged service composition in next generation network environment, it is necessary to have an approach that is capable to manage the difficulties of potential complexities due to service unavailability and network failures. In response to these challenges, we propose a converged service composition (CSC) framework having a management function that uses case-based reasoning (CBR) for handling services unavailability and/or network failures during the service composition process.